PENGARUH KOMPOS KOTORAN SAPI TERHADAP BEBERAPA SIFAT KIMIA TANAH INCEPTISOL DAN PERTUMBUHAN TANAMAN JAGUNG PULUT (Zea mays var. ceratina) - SAPUTRA, DAWAN DANDI; GINTING, SAHTA; NAMRIAH, NAMRIAH; DARWIS, DARWIS; ALAM, SYAMSU; RESMAN, RESMAN (Jurnal Agroteknos, 2022)
This study aims to determine the effect of the use of Inceptisol soil on the coast of Napabalano Subdistrict and the application of cow dung compost as a planting medium on the growth of Pulut maize (Zea mays var. ceratina) and determine the best dose of cow dung compost on the utilization of Inceptisol soil on the coast of Napabalano District against maize growth. This research took place in October-January 2022. This study used a Randomized Block Design (RBD) with five treatments, namely without cow dung compost (P0); cow dung compost 100 g polybag-1 (P1); cow dung compost 200 g polybag-1 (P2); cow dung compost 300 g polybag-1 (P3); cow dung compost 400 g polybag-1 (P4), repeated four times to produce 20 experimental units. The variables observed were nutrient levels of N, P, and K in Inceptisol soil on Napabalano District's coast and plant growth, including plant height and number of plant leaves. The results showed that cow dung compost increased the N-total nutrient content from 0,072% to 0,11%, P-total from 20,34 mg 100g-1 to 29.29 mg 100g-1, and K-total 21,24 mg100g-1 to 30,60 mg100g-1. Giving cow dung compost, 400 g polybag-1 significantly increased plant height and the number of plant leaves compared to other treatments.